Endoscopic findings of Helicobacter pylori gastritis in children and young adults based on the Kyoto classification of gastritis and age‐associated changes. Issue 10 (27th August 2021) - Hojo, Mariko; Nagahara, Akihito; Kudo, Takahiro; Takeda, Tsutomu; Ikuse, Tamaki; Matsumoto, Kohei; Ueda, Kumiko; Ueyama, Hiroya; Matsumoto, Kenshi; Asaoka, Daisuke; Shimizu, Toshiaki
Abstract: Background and Aim: We aimed to evaluate endoscopic findings of Helicobacter pylori ( H. pylori )‐positive children and young adults based on the Kyoto classification, and to examine if there are age‐associated changes in H. pylori ‐positive gastritis. Methods: H. pylori ‐positive patients under 40 years old who underwent upper gastrointestinal endoscopy from 1 April 2009 to 15 February 2017 were included. Subjects were classified into the Pediatric (<20 years) and Young adult groups (20–39 years). The patients' endoscopic photographs were retrospectively re‐evaluated based on the Kyoto classification. We compared endoscopic findings between the two groups and examined alterations in the findings of H. pylori ‐associated gastritis in 5‐year age groups. Results: Forty‐three and 163 subjects were classified into the Pediatric and Young adult groups, respectively. In the Pediatric group, nodularity was seen in the majority (93.0%); other endoscopic findings in order of decreasing frequency included mucosal swelling (32.6%), spotty redness (25.6%), diffuse redness (18.6%), and atrophy (9.3%). In the Young adult group, endoscopic findings included atrophy (66.9%), mucosal swelling (49.7%), spotty redness (39.3%), nodularity (31.9%), and diffuse redness (30.3%). The difference in prevalence of nodularity or atrophy between the two groups reached statistical significance ( P  < 0.0001 each). The rate of nodularity decreased with increasing age in the Young adult group. The rate of atrophy was 33% in young adult patients aged 20–24, and the rate increased to >65% in patients over age 25. Conclusion: H. pylori ‐positive children had endoscopic findings besides nodularity based on the Kyoto classification. The prevalence of atrophy increased in patients over age 20. Abstract : Helicobacter pylori ‐positive children had endoscopic findings besides nodularity based on the Kyoto classification. In the Young adult group, the prevalence of nodularity decreased with increasing age, and the prevalence of atrophy was over 65% in patients aged 25 years and over.